Quaternary Ammonium-Free Membranes for Water Electrolysis with 1 m KOH - 아스리딘 다얀; Muhammad Luthfi Akbar Trisno; Yang Chaeyeon; Kraglund, Mikkel Rykær; Almind, Mads Radmer; Hjelm, Johan; Jensen, Jens Oluf; Aili, David; Park, Hyun S.; Henkensmeier, Dirk (Wiley-VCH Verlag, 2023)
While anion exchange membrane (AEM) water electrolysis has many advantages, its commercialization is impeded by the low alkaline stability of most AEM, due to the fragility of quaternary ammonium groups. Ion solvating membranes (ISM) can be an alternative, but so far require high alkaline concentrations. Here, it is shown that sulfonation of polybenzimidazole results in ISM which swell strongly in 1 m KOH. Crosslinking with dibromoxylene controls the swelling, and after activation conductivities of >100 mS cm？1 can be reached in 1 m KOH. Stability in 1 m KOH at 80 °C is excellent: Conductivity remains unchanged and tensile strength and Young's modulus remains high over the test period of a half year. In an electrolyzer operating with 1 m KOH feed solution at 80 °C, a stable performance is achieved for over 500 h test without failure, suggesting that the high alkaline stability observed in ex situ tests is also achieved in the electrolyzer.